Comparative Advantage Following (CAF) development strategy, Aid for Trade flows and structural change in production - Sèna Kimm Gnangnon (Journal of Economic Structures, 2020)
This article investigates empirically the interaction between countries' Comparative Advantage Following (CAF) development strategy and Aid for Trade (AfT ) interventions in influencing the extent of structural change in production. Based on the Generalized Methods of Moments and an unbalanced panel dataset containing 81 countries over the period 1996-2016, the empirical exercise has shown that AfT flows are complementary with the CAF development strategy in generating a higher extent of structural change in production. Thus, higher amounts of AfT flows help promote structural change in production in countries that have adopted the CAF development strategy.
Keywords: F35; O11; O14; O2; O33; P59; 330; CAF development strategy; CAD development strategy; Aid for Trade; Structural change in production